Amplitude information based robust tracking method for multiple marine targets - Chao LIU; Zhiguo ZHANG; Jinping SUN (Tongxin xuebao)
A robust multi-Bernoulli filter based on the amplitude information of the target in sea clutter was proposed,in which the amplitude information of the target and sea clutter was exploited to improve the measurement likelihood.Therefore,the proposed approach could distinguish targets from clutter better when they were spatially close,which further enhanced the ability to track targets in marine radar detection applications.The simulation results of Swerling type Ⅰfluctuating targets tracking in K distributed sea clutter show that,the proposed algorithm is superior in performance to the robust multi-Bernoulli filter in terms of state estimation,cardinality estimation,as well as clutter rate estimation.